Service User Experiences of Integrating a Mobile Solution (IMPACHS) Into Clinical Treatment for Psychosis. (April 2021) - Austin, Stephen F.; Frøsig, Anna; Buus, Niels; Lincoln, Tania; von Malachowski, Alissa; Schlier, Bjorn; Frost, Mads; Simonsen, Erik
Innovative technological solutions are increasingly being introduced into psychotherapy. Understanding service user perspectives is a key aspect in adapting this technology to treatment. This study investigated service users' personal experience of the utility, challenges, and rewards of using an mHealth solution in cognitive behavioral therapy for psychosis (CBTp). People participating in an early intervention program for psychosis ( n = 16) utilized the mHealth solution for up to 6 months. Semi-structured qualitative interviews were conducted to capture participant experiences, and quantitative data were collected on psychopathology, usage, and quality of the solution. The solution was widely accepted and utilized in treatment. Four dominant themes were constructed from the interviews: (a) Accessibility and supporting recall, (b) Promotion of dialogue with the therapist, (c) Encouraging reflection, and (d) Factors that affected engagement with the solution. The mHealth solution was perceived as facilitating psychotherapeutic processes and supported underlying CBTp treatment principles.